Effects of Delay in Construction Phase of Oil and Gas Projects in Malaysia - Suppramaniam, S Umeesh Kumar; Ismail, Syuhaida (Journal of Advanced Research in Business and Management Studies, 2020)
Delay in project is a universal phenomenon and the effects of the delay can affect all involved stakeholders. Thus, most project management companies managing Engineering, Procurement, and Construction (EPC) contracts in oil and gas projects are optimising the activities to avoid any delays which can affect the entire project negatively. It is important to understand how the delay in the construction phase affects the oil and gas projects negatively and how bad the effects can be. This paper aims to investigate the effects of delay in the construction phase of the oil and gas projects in Malaysia. A systematic literature review (SLR) from various sources through books, conference proceedings, project management documents, and oil and gas industry journals were made to write this paper. Some effects of delays were categorised as the main effect and some as the sub effect. This initial study is based purely on literature review, comparison of similar cases, cross referencing, and critical judging. The effects of delay in the construction phase specific to the oil and gas projects in Malaysia should be further researched with focus only in the Malaysian projects and industry players in order to derive a good delay mitigation plan at later stage.